2014
DOI: 10.1371/journal.pone.0106110
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Immunogenicity of Induced Pluripotent Stem Cells Derived from Sertoli Cells

Abstract: Sertoli cells constitute the structural framework in testis and provide an immune-privileged environment for germ cells. Induced pluripotent stem cells (iPS cells) resemble embryonic stem cells (ES cells) and are generated from somatic cells by expression of specific reprogramming transcription factors. Here, we used C57BL/6 (B6) Sertoli cells to generate iPS cells (Ser-iPS cells) and compared the immunogenicity of Ser-iPS cells with iPS cells derived from mouse embryonic fibroblast (MEF-iPS cells). Ser-iPS ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Although they discovered that initially low passage SC-iPSCs were less immunogenic in vivo than MEF-iPSCs, the observed reduced immunogenicity was lost following extended culturing. Similar to the finding described by Polo et al, [38] these immune-privileged cells still exhibited reduced immunogenicity when compared to MEF-iPSCs [46]. This is likely due to epigenetic memory from the donor cell impacting the immunogenicity of the derived iPSCs.…”
Section: The Importance Of Cell Source For Ipscssupporting
confidence: 83%
See 1 more Smart Citation
“…Although they discovered that initially low passage SC-iPSCs were less immunogenic in vivo than MEF-iPSCs, the observed reduced immunogenicity was lost following extended culturing. Similar to the finding described by Polo et al, [38] these immune-privileged cells still exhibited reduced immunogenicity when compared to MEF-iPSCs [46]. This is likely due to epigenetic memory from the donor cell impacting the immunogenicity of the derived iPSCs.…”
Section: The Importance Of Cell Source For Ipscssupporting
confidence: 83%
“…For example, Wang et al tested whether the low immunogenicity of Sertoli cells (SC) was maintained in SC-derived iPSCs, either freshly isolated or after extensive in vitro passaging, as well as in the in vivo setting [46]. They demonstrated that SC-derived iPSCs resulted in a high frequency of teratoma formation when injected into syngeneic B6 mice, as compared to MEF-iPSCs and ES cells; suggesting that SC-derived iPSCs elict a blunted immune response thereby allowing for more efficient teratoma formation.…”
Section: The Importance Of Cell Source For Ipscsmentioning
confidence: 99%
“…Other groups have reported that iPSC derivatives showed different degrees of immunogenicity . In particular, those groups showed that iPSC‐derived cardiomyocytes and endothelial cells can induce more prominent immune responses in syngeneic mice compared with hepatocytes, neuronal cells and bone marrow cells .…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have reported that iPSC derivatives showed different degrees of immunogenicity. 7,20,21 In particular, those groups showed that iPSC-derived cardiomyocytes and endothelial cells can induce more prominent immune responses in syngeneic mice compared with hepatocytes, neuronal cells and bone marrow cells. 6 During the reprogramming processes in iPS cells from somatic cells, epigenetic changes can induce the expression of minor antigens, which can possibly directly or indirectly lead to the rejection of iPSC-derivatives in syngeneic mice.…”
Section: Discussionmentioning
confidence: 99%
“…From late in vitro passages, Ser‐iPSCs behaved similarly to MEF‐iPSCs in vivo . It appears that immune‐privileged Sertoli cells gave rise to Ser‐iPSC, which retained some somatic memory of their origin, a feature that makes them a good candidate for regenerative medicine …”
Section: Pluripotency/malignancy Teratoma Assaymentioning
confidence: 99%